KONJUNGSI KARANGAN SISWA KELAS X SMAN 1 REBANG TANGKAS TP 2012/2013 - Esi Pitriani; Siti Samhati; Eka Sofia Agustina (Jurnal Kata (Bahasa, Sastra, dan Pembelajarannya), 2013)
This research concerned to the conjunction in the students’ written at first grade of SMA Negeri Rebang Tangkas academic year 2012/2013. The objective of this research is to describe the uses of conjunction in students’ written. This research used qualitative description as the research method. The writer collected the data from 40 students’ written. The students used 276 coordinative conjunction with accuracy 233 and inaccuracy 43. Second, the students used 185 subordinative conjunction with accuracy 126 and inaccuracy 59. Third, the students used 3 correlative conjunction with accuracy 2 and inaccuracy 1. Forth, the students used 25 inter-sentences conjunction with accuracy 22 and inaccuracy 3, While, the students used 5 extern-sentences conjunction with accuracy 2 and inaccuracy 3.Masalah yang dibahas pada penelitian ini adalah konjungsi pada karangan siswa kelas X SMA Negeri Rebang Tangkas tahun pelajaran 2012/2013. Penelitian bertujuan mendeskripsikan penggunaan konjungsi dalam karangan siswa. Metode penelitian adalah deskriptif kualitatif. Sumber data dalam penelitian berupa teks hasil karangan siswa yang berjumlah 40 siswa. Penggunaan konjungsi koordinatif 276 ketepatan 233 dan ketidaktepatan sebanyak 43. Kedua, konjungsi subordinatif 185 ketepatan 126 dan ketidaktepatan 59. Ketiga, konjungsi korelatif 3 ketepatan sebanyak 2 dan ketidaktepatan 1. Keempat, konjungsi antarkalimat sebanyak 25 ketepatan 22 dan ketidaktepatan 3. Sedangkan konjungsi intrakalimat 5 ketepatan 2 dan ketidaktepatan 3.Kata kunci: konjungsi, penggunaan, siswa.